Level of knowledge and consumption of quinoa, kiwicha, maca and soybean among students of the National University of Jaén - Jiménez-Cordova, Yaniny Sofia (2024)
College students experience challenges that change their eating habits and patterns. The freedom to make decisions, especially in food choices, and independent living create new nutritional challenges (De Piero et al., 2015). The research applied a survey to evaluate the level of knowledge and consumption of quinoa (Chenopodium quinoa willdenow), kiwicha (Amaranthus caudatus), maca (Lepidium meyeeni) and soybean (Glycine max), and their interrelationship, in students of the National University of Jaén, with a sample of 329 students of the five professional careers of the semester 2023-I, was statistically analyzed with Kendall's correlation coefficient. A low level of consumption was found: quinoa (65.65%), kiwicha (73.86%), maca (64.44%) and soybeans (59.88%). For the four products, men tend to consume more than women (51%-54% and 45%-48%, respectively), and those with an income below S/. 1025 have a higher consumption (77%-79%). The preference for consuming these products in drinkable form is mainly due to family traditions. A low level of knowledge was also found for quinoa (62.31%), kiwicha (60.79%), maca (61.70%) and soybeans (60.79%). A positive correlation with a weak degree of association (0.29 to 0.35) was found between the level of knowledge and consumption.